Development of Madrasah Supervisor Professionalism in Order to Improve The Quality of Madrasah (Research on the Madrasah Supervisor Working Group of the Office of the Ministry of Religion, Regency and City of Tasikmalaya) - Sopwan, Agus; Mahmud, Mahmud; Erihadiana, Mohamad; Karman, Karman (Green Publisher Indonesia, 2024)
This study aims to examine the development of the professionalism of madrasah supervisors in order to improve the quality of madrasahs. The method used is a qualitative approach with a descriptive method, where data is collected through interviews, observations, and documentation. The data analysis technique involves data reduction, data presentation, and conclusion drawing. The results of this study reveal several key points: 1) The planning of supervisor development is carried out through recruitment based on administrative, competence, and qualification requirements, including the preparation of scientific papers and meeting credit score standards; 2) The implementation is conducted through supervision programs, which include the development of teacher competencies, monitoring graduate competency standards, content standards, process standards, and assessment standards, as well as teacher performance evaluations; 3) The evaluation of professional development has been continuously performed in accordance with the planned objectives and the established assessment standards; 4) Follow-up actions are conducted both individually and in groups; and 5) The design of this research is called the